Fundamental and applied aspects of chemically modified surfaces. Jonathan P. Blitz y Charles B. Little, editores. [Proceedings: 7th International Symposium on Chemically Modified Surfaces (24-28 jun, 1998) at Evanston, Illinois]. The Royal Society of Chemistry. Milton Road, Cambridge (1999). 399 p. - Kong Moreno, Maynard (2000)
El artículo no presenta resumen.